The relationship between gadget use and headache among student - Tarigan, Miranda br; Fresia, Ana; Lubis, Adhayani (Buletin Kedokteran & Kesehatan Prima, 2024)
Gadget usage has become an integral part of the lives of students in the modern era, including Indonesia, where there has been a significant increase in gadget users. This study aims to investigate the relationship between the frequency of gadget use and the occurrence of headaches among medical students at Universitas Prima Indonesia in 2022. Using a quantitative descriptive approach and cross-sectional research design, this study analyzed the data collected through a questionnaire. Chi-square tests were used to examine the relationship between the independent variable, gadget usage, and the dependent variable, the occurrence of headaches. The results indicated that tension-type headaches were the most common type experienced by students, followed by migraines. However, some students reported cluster headaches, while others did not experience any headaches. The most significant finding was the strong correlation between the frequency and duration of gadget use and the increased risk of developing headaches. These findings underscore the importance of recognizing the negative health consequences of excessive gadget use, particularly among students. Therefore, there is a need for strategies to manage gadget usage wisely to prevent headaches that may disrupt academic performance and overall quality of life.